The conservative turn : Lionel Trilling, Whittaker Chambers, and the lessons of anti-communism - Kimmage, Michael (Harvard historical studies, 2009)
The Conservative Turn tells the story of postwar America's political evolution through two fascinating figures: Lionel Trilling and Whittaker Chambers, who went on to intellectual prominence, sharing the questions, crises, and challenges of their generation. Kimmage argues that the divergent careers of these two men exemplify important developments in postwar American politics: the emergence of modern conservatism and the rise of moderate liberalism.